KAJIAN NEW HISTORICISM NOVEL KUBAH KARYA AHMAD TOHARI - Sahliyah, Chalifatus (Universitas Pendidikan Indonesia, 2017)
This study aims to describe the representation of (1) Indonesian history, (2) culture, and (3) economy in the novel Kubah. The novel, written by Ahmad Tohari, is analyzed using New Historicism, in which non-literary texts are drawn on to understand the literary text being analyzed. The research procedure involves: (1) parallel reading technique, that is reading both the novel and the non-literary texts simultaneously, (2) analysis, as shown in the data presentation and discussion, involving parallel reading in which events in the novel are highlighted and related to the non-literary texts; and (3) drawing conclusion based on the analysis of historical, cultural and economic facts contained in the novel, which have been cross-checked against the non-literary texts of similar topics. The results of the analysis include: (1) historical representation of the recruitment, the hiding, the arrest, and the exile of PKI (Indonesian communist parti) members before and after the 1965 tragedy; (2) cultural representation of the Javanese, as indicated in the language use, figurative speech and the Javanese tembang; and (3) economic representation as signaled by the weakening of the economic condition after the 1965 tragedy. The use of new historicism in analyzing the novel Kubah is expected to broaden the readers’ historical knowledge, thus avoiding the bitter experiences in the past to repeat themselves in the future.Keywords: new historicism, representation, history, culture, economy